Determinants of mortality after stereotactic radio-ablation for ventricular tachycardia. Results from the international MUSIC consortium. (19th May 2022) - Cochet, H; Maury, P; Whitaker, J; Woods, C; Gandjbakhch, E; Bredfeldt, J; Mak, R; Sauer, W; Juhoor, M; Sermesant, M; Sacher, F; Bogun, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Council Background: SBRT is currently restrained to the most severe patients with drug- and catheter ablation-refractory VT, often associated with advanced heart failure. Purpose: To analyze the determinants of mortality after SBRT for VT. Methods: Patients with drug- and catheter ablation-refractory VT underwent imaging prior to SBRT. The inHEART technology was used to create image-based 3D models of substrate, cardiac anatomy, and organs at risk (coronaries, phrenic nerve, GI tract, AV node). In MUSIC software (IHU Liryc-Inria), 3D models were fused with prior EP maps, and SBRT targets were interactively drawn in 3D by the referring EP cardiologist. Transmural target volumes and organs at risk were fused with a 4D planning CT and used to plan SBRT in Eclipse (Varian). SBRT was delivered with either Truebeam or Edge systems (Varian), at a total dose of 25 Gy in a single session. The determinants of adverse outcomes after SBRT were analyzed. Results: 30 pts from 7 centers were included (age 70±10, 90% men). Mean LVEF was 26±9%. The VT etiology was ischemic in 67%, and non-ischemic or mixed in 47%. Patients had undergone a mean of 1.7±1.2 prior failed catheter ablation procedures. SBRT was delivered on median planning treatment volumes (PTVs) of 96[63-149] mL. Complications attributed to SBRT were observed in 2/30 (7%), none of which were fatal (heart failure and pneumonitis, both managed with steroids). Over a median FU of 4[2-8] months, death or heart transplant occurred in 11(37%) pts, attributed to VT recurrence in 4(13%), and heart failure in 7(23%). On univariate analysis, patients experiencing death or transplant after SBRT were older (77±6 vs. 66±9 years, P=0.001) and showed lower LVEF (22±6 vs. 29±10%, P=0.03). In contrast, mortality or transplant did not relate to the underlying VT etiology (P=0.30), the number of prior catheter ablations (P=0.20), the pre-SBRT VT burden (P=0.20) and the SBRT treatment volume (P=0.18). Conclusion: In patients with severe drug- and catheter ablation-refractory VT undergoing cardiac SBRT, mortality is most often due to non-arrhythmic causes, and is more driven by age and LV dysfunction than by the VT substrate, pre-SBRT arrhythmia burden, and SBRT treatment volume.